Development of Vocational Learning E-Modules In Arts And Culture Subjects in Package B SPNF SKB Pasaman Regency - Mahdona, Siska Okta; Dasa Putri, Lili (Universitas Negeri Padang, 2025)
This research is motivated by the low learning outcomes of students which is suspected by the lack of learning media and teaching materials to support the learning process itself, especially in the Cultural Arts subject in Package B, especially Traditional Dance material. One of the innovations that can be made in learning to make the learning process more interesting is to develop an e-module. This study aims to determine the validity, practicality and effectiveness of vocational learning e-modules in Cultural Arts subjects in Package B SPNF SKB Pasaman Regency. This type of research is research and development or better known as R&D with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model which is carried out to produce new products oriented to vocational learning. The test subjects in this study are students of Package B class VIII for the 2023/2024 school year. This study uses a data collection instrument in the form of a questionnaire with a Likert scale model. The results of the study showed that the e-module was included in the very valid category with a percentage score of 89.3%. The results of practicality from students were obtained with a score of 89.8% with the category of very practical. The learning modules developed in the effectiveness test through pretest and posttest activities experienced a significant increase of 90% with the effective category. Based on these results, it can be concluded that the vocational learning e-module in the Arts and Culture subject in Package B SPNF SKB Pasaman Regency is declared valid, practical and effective to be used in the learning process.